Exploring High School EFL Teachers' Experiences with Magic School AI in Lesson Planning: Benefits and Insights - Setyaningsih, Endang; Asrori, Muhammad; Ngadiso; Sumardi; Zainnuri, Hasan; Hariyanti, Yuni (Universitas Hamzanwadi, 2024)
Advancements in artificial intelligence (AI) are reshaping education, yet its role in lesson planning warrants further exploration. This study examines how Indonesian high school English as a Foreign Language (EFL) teachers integrate MagicSchool AI, a generative AI tool, into lesson planning, revealing opportunities and challenges. Data from 38 teachers, collected through post-workshops open-ended questionnaires, and focus group interviews, highlight AI's dual potential: while it accelerates lesson planning, supports differentiated instruction, and fosters creativity, it also necessitates critical teacher oversight, effective prompt-engineering skills, and significant adaptation to align with classroom dynamics. Teachers emphasized AI’s value in reducing workloads and generating diverse instructional ideas but noted that its outputs often lack readiness for immediate use, requiring refinement to ensure pedagogical soundness. These findings underscore the importance of targeted training and professional development to equip teachers with the skills to navigate AI tools effectively. This study emphasizes the critical balance between human expertise and technological efficiency by framing AI as a collaborative ally rather than a replacement for educators. It contributes to the growing discourse on AI in education, offering insights into optimizing human-AI collaboration for innovative, contextually relevant, and impactful teaching practices. This research invites educators and policymakers to envision AI as a transformative force, capable of bridging innovation with pedagogical integrity to shape the future of education.